IGF-I levels rise and GH responses to GHRH decrease during long-term prednisone treatment in man. - Borges, M; Pinto, A; DiNinno, F; Camacho-Hübner, C; Grossman, A; Kater, C; Lengyel, A (1999)
Glucocorticoid excess is associated with a blunted GH response to GHRH. IGF-I levels in hypercortisolism are controversial and have been reported as low, normal or high. The aim of this study was to evaluate longitudinally time-dependent changes in the GH response to GHRH, IGF-I, IGFBP-3 and albumin values in patients during corticotherapy. Six patients received GHRH before and after one week and one month of prednisone administration (20-60 mg/d, orally). IGF-I, IGFBP-3 and albumin were determined in each test, at time 0. Ten normal controls were also evaluated in one occasion. There were no differences in basal GH values, GH response to GHRH, IGF-I and IGFBP-3 levels between controls and patients before starting corticotherapy. Albumin (g/l; mean+/-SE) values were lower in patients before treatment (31+/-4) than in controls (43+/-1). After one week of prednisone administration there was a significant decrease in peak GH (microg/l) levels (before: 18.8+/-7.4; 1 week: 5.0+/-1.3), which was maintained after one month (8.1+/-3.5). IGF-I (microg/l) levels increased significantly, from 145+/-23 to 205+/-52 after one week of therapy, reaching levels of 262+/-32 after one month. IGFBP-3 (mg/l) values did not increase significantly (before: 2.1+/-0.2; 1 week: 2.5+/-0.3; 1 month: 2.8+/-0.2). Albumin levels showed a significant rise both after one week (36+/-4) and one month (42+/-3) of corticotherapy. In summary, we observed a marked decrease in the GH response to GHRH after one week and one month of prednisone administration associated with an increase in circulating IGF-I and albumin values. The physiological implications of these findings are still uncertain. It is possible that glucocorticoids increase hepatic IGF-I and albumin synthesis, although other mechanisms may have a role.